Evaluation of hearing in patients with psoriasis considering the disease severity - Hapa, Aslı; Süslü, Nilda; Karaduman, Ayşen; Budak, Bilgehan; Ersoy Evans, Sibel; Sennaroğlu, Levent (ENT Updates, 2016)
Objective: Nowadays, psoriasis is accepted to be an autoinflammatory/ autoimmune disease. As a result of chronic inflammation, psoriasis is widely investigated for associated diseases and comorbidities. However, there are limited data about the effects of psoriasis on hearing functions. The aim of the study was to investigate prospectively if patients with psoriasis have sensorineural hearing loss and the effect of the disease severity on hearing levels. Methods: Overall, 50 patients (100 ears) with psoriasis and 45 healthy controls (90 ears) were included in the study. After otoscopic examination, pure tone air and bone conduction including high frequencies (500, 1000, 2000, 4000, 8000, and 16,000 Hz) and speech audiometry were performed to all participants. Results: Median pure tone average of the patients was significantly different than controls. Moreover, the frequency levels of patients with psoriasis for both of the ears were all significantly different from the control group. As the limitation of the study, patients were not investigated for psoriatic arthritis and sera from patients were also not investigated for anti-bodies for inner ear antigens such as anti-connexin 26, anti-DEP/CD148 and anti 68K. Conclusion: The possibility of inner ear involvement should be kept in mind in psoriasis as a result of chronic systemic inflammation. Patients with psoriasis may be evaluated with audiometry periodically even if they do not exhibit any hearing problems.